Effect of various hepatectomy procedures on circulating tumor cells in postoperative patients: a case-matched comparative study - Lei, YongRong; Wang, XiShu; Tian, YiChen; Xu, Rong; Pei, Jun; Fu, YuNa; Sun, Heng; Wang, YaNi; Zheng, Ping; Xia, Feng; Wang, JianHua (Frontiers in Medicine, 2023)
This study aimed to investigate the incidence of circulating tumor cells (CTCs) in patients with hepatocellular carcinoma (HCC) before and after surgery, and compare the postoperative CTC counts and phenotypes between patients who underwent open liver resection (OPEN) and laparoscopic liver resection (LAP). Thirty-two consecutive HCC patients who underwent laparoscopic liver resection between September 2015 and May 2022 were included in the study. Clinical and pathological data of all patients were obtained from a computer database. Patients in the OPEN group were matched one-to-one with patients who underwent open liver resection during the same period, based on age, sex, tumor size, number of tumors, tumor location, hepatitis B surface antigen (HBsAg) positivity, alpha-fetoprotein (AFP) levels, TNM staging, and Child-Pugh staging. CTCs were enriched and characterized using the Can-Patrol CTC enrichment technology, and classified based on epithelial-mesenchymal transition phenotypes. The primary endpoint was disease-free survival (DFS), and the impact of total CTC counts and CTC phenotypes on prognosis was analyzed using Kaplan-Meier methods and multivariate Cox proportional hazards models. The study results showed that the average age of the 64 patients with primary liver cancer was 52.92 years (range: 23-71 years), and 89.1% were male. The clearance rate of postoperative CTCs was higher in the OPEN group. Compared with the OPEN group, the LAP group had significantly increased residual total CTCs and CTC phenotypes (P=0.017, 0.012, 0.049, and 0.030), which could potentially increase the likelihood of metastasis (P=0.042). Kaplan-Meier analysis showed that DFS was significantly associated with several clinical and pathological risk factors, including Barcelona Clinic Liver Cancer (BCLC) staging, tumor size, and vascular invasion. Among them, BCLC staging (P=0.043, HR (95%CI)=2.03 (1.022-4.034)), AFP (P=0.007, HR (95%CI)=1.947 (1.238-3.062)), positive CTC counts (P=0.004, HR (95%CI)=9.607 (2.085-44.269)), and vascular invasion (P=0.046, HR (95%CI)=0.475 (0.22-1.023)) were significantly correlated with DFS. Conclusion: Laparoscopic liver resection has the ability to increase the number of epithelial, mixed, and mesenchymal circulating tumor cells (CTCs) compared to traditional open liver resection. After surgery, the total CTCs, epithelial CTCs, and mixed CTCs were significantly increased in the LAP group, suggesting potential unfavorable factors in CTC release for LAP.